LATIN AMERICAN FOREIGN POLICY AND THE COMMUNITY OF LATIN AMERICAN AND CARIBBEAN STATES - Llenderrozas, Elsa (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The creation of the Community of Latin American and Caribbean States (CELAC) in February, 2010, reconfigures a new step in the process of regional politics concert. As a result of the convergence of different regional instances, fundamentally the Grupo Río and the Latin American and Caribbean Summit on Integration and Development (CALC), and increasing will to cooperate, a new mechanism is order to overcome the subregional level is created, activating multilevel fora and reinforcing the tendency to build multidimensional agendas. This paper is divided in three parts. The first one analyzes the general objectives of the group and the regional representation or communication will be highlighted; the second part deals with the tematic agendas, their scopus and limits; and in the third section the external axis that the bloc has tracked until now will be drafted, along with their obstacles and possibilities. This work ends up with some considerations of prospective character.